2015
DOI: 10.1371/journal.pntd.0003537
|View full text |Cite
|
Sign up to set email alerts
|

Sm29, but Not Sm22.6 Retains its Ability to Induce a Protective Immune Response in Mice Previously Exposed to a Schistosoma mansoni Infection

Abstract: BackgroundA vaccine against schistosomiasis would have a great impact in disease elimination. Sm29 and Sm22.6 are two parasite tegument proteins which represent promising antigens to compose a vaccine. These antigens have been associated with resistance to infection and reinfection in individuals living in endemic area for the disease and induced partial protection when evaluated in immunization trials using naïve mice.Methodology/principals findingsIn this study we evaluated rSm29 and rSm22.6 ability to induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…When C57Bl/6 mice were vaccinated with Sm22.6 and challenged 15 days after the last boost, they showed a mean 34.5 % protection [ 59 ]. In contrast, when the antigen was administered to Balb/c mice that were challenged 30 days after the last boost, the protection elicited was 0 and 18 % [ 60 ]. A similar pattern was observed with Sm29 where 51 % protection was observed after a challenge of C57Bl/6 mice at 15 days after the last boost [ 61 ] and 0 % protection after a challenge of Balb/c mice at 30 days [ 60 ].…”
Section: Vaccine Antigen Testing In the Mousementioning
confidence: 99%
“…When C57Bl/6 mice were vaccinated with Sm22.6 and challenged 15 days after the last boost, they showed a mean 34.5 % protection [ 59 ]. In contrast, when the antigen was administered to Balb/c mice that were challenged 30 days after the last boost, the protection elicited was 0 and 18 % [ 60 ]. A similar pattern was observed with Sm29 where 51 % protection was observed after a challenge of C57Bl/6 mice at 15 days after the last boost [ 61 ] and 0 % protection after a challenge of Balb/c mice at 30 days [ 60 ].…”
Section: Vaccine Antigen Testing In the Mousementioning
confidence: 99%
“…In schistosomiasis, several immunization strategies with different parasite antigens have been developed and the most promising results have demonstrated the participation of memory cells in the context of protection or reduction of tissue damage caused by the presence of the parasite …”
Section: Discussionmentioning
confidence: 99%
“…Vaccination with rSjTPI-LD1 induced a significantly high level of both anti-rSjTPI and anti-rSjLD1-specific IgG antibodies at all time points post-vaccination compared with controls ( Figure 4.1). This is a feature common to other schistosome vaccine candidates tested in mice [280,281]; moreover, another study showed that IgG antibodies are important for the protection against schistosomes [282]. Here, the anti-rSjTPI and anti-rSjLD1 IgG antibody response peaked at week 6 after the last booster vaccination with the highest titers of 1:102,400 and1: 204,800 obtained, respectively (Figure 4.2).…”
Section: Discussionmentioning
confidence: 57%
“…A recent report [280] has suggested that undertaking anti-schistosome vaccine trials in mice may be problematic and may generate spurious protective data. The report questioned whether such trials in mice are able to effectively determine whether any significant worm reduction data obtained are due to acquired immunity induced by a candidate vaccine or are rather due to mouse vasculature physiology that impacts on schistosome worm survival [279].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation